STABILITY AND DYNAMIC ANALYSES OF PIPE CONVEYED FLUID STIFFENED BY LINEAR STIFFNESS ELEMENT USING FINITE ELEMENTS METHOD (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2022)
Different types of dynamic instability of the system occur when the flow velocity exceeds a specific value; thereby the problem of dynamic instability of the pipe conveyed flow became shining. Several effective parameters play an important role in stabilizing the system, such as stiffness addition. In this search, dynamic analysis of pipe conveying fluid stiffened by linear spring was studied using the finite element method. The effect of stiffness addition (linear spring) and the effect of spring location was deeply studied. Also, the effect of flow velocity on the dynamic stability of the system was taken into the consideration. It was observed that there is a critical flow velocity after which the system loses its stability. There is a critical spring constant at which the dynamic behavior becomes more sensitive. Also, there is a specific spring location (effective location) so the spring offers the best results for the frequency of the system. Effective spring locations depend on the flow velocity and spring constant itself. The effective spring location was found to be arranged from x/l= 0.7 to 1.